Des données textuelles et planimétriques à l’analyse des dynamiques paysagères et foncières. Le cas de Blandy-les-Tours (Seine-et-Marne) du XVIe au XIXe siècle - Albane Rossi (Bulletin du Centre d’Études Médiévales d’Auxerre)
This doctoral study is largely based on the parallel processing of textual and planimetrics data, be they modern or contemporary, incorporated into a geographical information system. The relevant documents (a 16th-century terrier, a terrier linked to a 18th-century plan and the 1845 Napoleon’s cadaster) which includes the consistent recording of plots of land and tenants/owners, present a lot of information on the rural space structuring : land ownership, its own representatives, the space they manage and their way of seeing it. However, each document describe a different space reality, depending on the relevant period. By working both with a micro historical scale and the long-term perspective, it’s the daily practice as well as the actors’ perception, the research for potential breakdowns in the land use along with the space management that will be considered. In this paper, we will expose the acquisition methods, the data processing and eventually some outcomes.